2011
DOI: 10.1007/s10661-011-2272-7
|View full text |Cite|
|
Sign up to set email alerts
|

Mobility of selected trace elements in Mediterranean red soil amended with phosphogypsum: experimental study

Abstract: Soil amendment by phosphogypsum (PG) application becomes of increasing importance in agriculture. This may lead, however, to soil, plant, and groundwater contamination with trace elements (TEs) inherently present in PG. Monitoring of selected TEs (Pb, Zn, Cu, and Cd) distribution and mobility in a Mediterranean red soil profile has been performed in soil parcels applied with PG over a 16-month period. Concentrations were measured in soil and plant samples collected from various depth intervals at different poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…The pH values of the soil samples lie between 7.5 and 8.3, and thus are considered calcareous, which is the case of many soils belonging to floodplain of humid regions (Foth 1990), such as the Qaraaoun reservoir. The basic pH value is an indication of high calcareous content in Q1 (Table 4 and 5), the same pH variation range in the soil profile was indicated by Kassir et al (2012) in a study done in North Lebanon of a clayey soil. The 40-50cm profile of Q2 has the lowest EC, TDS and pH KCl values (Table 4); the values are significantly different from values of other depths.…”
Section: Soil and Sediment Analytical Experimentationsupporting
confidence: 64%
“…The pH values of the soil samples lie between 7.5 and 8.3, and thus are considered calcareous, which is the case of many soils belonging to floodplain of humid regions (Foth 1990), such as the Qaraaoun reservoir. The basic pH value is an indication of high calcareous content in Q1 (Table 4 and 5), the same pH variation range in the soil profile was indicated by Kassir et al (2012) in a study done in North Lebanon of a clayey soil. The 40-50cm profile of Q2 has the lowest EC, TDS and pH KCl values (Table 4); the values are significantly different from values of other depths.…”
Section: Soil and Sediment Analytical Experimentationsupporting
confidence: 64%
“…They had posited that environmental risk by radioactivity in Shistos area would be minimized by simple thick soil cover and geomembrane. Kassir et al [12] had attempted to valorize PG in soil amendment via the assessment of selected trace elements in Mediterranean red soil from Lebanon. They concluded that soil amendment by PG is feasible and viable due to low environmental impact of trace elements, that remained below the threshold limits required by relevant Lebanese regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Management of these large quantities is one of the most challenging environmental problem in many countries [14]. To limit the potential impact of those by-products, several studies have been undertaken with an attempt to valorize PG in various industrial and agricultural applications, including building materials [15][16][17][18][19], agricultural fertiliser [20][21][22] and soil amendments [12,23,24]. The long-term management of PG is directly related to the problem of potentially toxic elements leaching.…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree with Pérez-López 18 , who reported that PG did not contain large amount of heavy metals and that addition of PG did not lead to soil contamination. Kassir et al 19 monitored the effect of PG application on heavy metals in Mediterranean red soil and showing that the exchangeable and acid soluble contents of heavy metals in PG applied soil were higher than those in PG-untreated soil. Our study found that the application of 0.1% PG reduced the content of water-soluble fluorine, and the application of 1% or 10% PG significantly increased the content of water-soluble fluorine, indicating that the appropriate application of PG will not lead to soil fluorine pollution.…”
Section: Discussionmentioning
confidence: 99%